Türkiye’nin sosyal ve ekonomik tarihi (1071-1920) : “birinci uluslararası Türkiye’nin sosyal ve ekonomik tarihi kongresi” tebliğleri = Social and economic history of Turkey (1071-1920) : papers presented to the “first international congress on the social and economic history of Turkey” : Hacettepe University, Ankara Jully 11-13, 1977 (Ankara)
xvi, 396 s.